Exploring Martin Heidegger’s conceptions of phenomenology and transcendence: addressing the problem of religious fundamentalist violence - Sanni, John Sodiq (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.